The Madeiran laurel forest endemic Goodyera macrophylla (Orchidaceae) is related to American orchids - Thiv, Mike (2021)
Macaronesian laurel forests harbour many herbs and lauro phyllous trees with Mediterranean/European or Macaronesian affini ties. Traditionally, the origin of these taxa has been explained by the relict hypothesis interpreting these taxa as relics of formerly wide spread laurel forests in the European continent and the Mediterranean. We analysed the phylogenetic relationships of the Madeiran laurel forest endemic Goodyera macrophylla (Orchidaceae) using sequences from the nuclear ribosomal DNA Internal Transcribed Spacers (ITS) and plastid DNA regions. The results were incongruent, either the two Central American G. brachyceras and G. striata (ITS) or the North American G. oblongifolia (plastid DNA) were sister group to G. mac rophylla. Nonetheless, biogeographic analyses indicated an American origin of this nemoral laurel forest plant in the two data sets. Molecu lar clock analyses suggest a colonisation of Madeira in the span of the upper Miocene/lower Pliocene to the Pleistocene. Although the relict hypothesis cannot be ruled out by our data when assuming extinction events on the European and northern African mainland, dispersal from Central or North America to the archipelago of Madeira is a much more likely explanation of the data.